Lightweight identity authentication scheme for IoT devices based on blockchain. Issue 1 (February 2021) - Ma, Wanli; Zhang, Qi; Ma, Junwei; Xue, Honglin; Hao, Xiaowei; Li, Haitao; Jia, Weidong; Meng, Yaning; Wen, Zhifang; Zhang, Jianliang
Abstract: Aiming at the resource limitation and security problems of Internet of things devices, a lightweight identity authentication scheme is proposed. In the scheme, the identity authentication model is designed, and the model is implemented by using the blockchain smart contract. Through the analysis, the scheme can effectively complete the identity authentication under the condition of limited equipment resources.